When the Beast is Not the Enemy: Myths and Ecology World-Making in Comparative Literature - Ghanesya Hari Murti; Andang Subaharianto; Erna Cahyawati; Dyah Purwita Wardani; Imam Basuki (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2026)
Myth is an important context for societies to negotiate the relationship between humans, nature and values, based on a comparative literary analysis of mythological animals in Eastern and Western Traditions. In Eastern (Asian) traditions mythological figures such as Antaboga, Nyai Roro Kidul and Barong are considered ontological mediators and manifestations of the living ecological order. In Western traditions, by contrast, they are constructed as enemies, monsters or as existential threats to civilization in opposition. In these stories, mythological creatures are ecological boundaries, not hostile boundaries. Such traditions are diametrically opposed to the dominant Western literary paradigm, Beowulf, Moby-Dick and Argonaut, which prioritizes the conquest of monsters and the realization of narrative closure through conquest and control. Within the theoretical framework of this article, carefully grounded in literary form, temporality and the development of the literary canon, legendary creatures serve as vehicles for diverse perceptions of nature. One is founded on dominance and abstraction, the other on reciprocity and moderation. Eastern stories are structured in cycles. Nature’s balance is a dynamic and fragile process. There is no ultimate victory, and it must always be preserved. Meanwhile Western stories are linear and teleological and move toward a definitive end (such as possession or accumulation of wealth) once ecological barriers are removed.